Uji Daya Hambat Ekstrak Etanol Bunga Pepaya (Carica papaya L) terhadap Bakteri Klebsiella sp dan Shigella sp - Dwi Aprilia Anggraini; Norma Farizah Fahmi; Rizka Efi Mawli; Moh Saiful Hakiki (LPPM Universitas Abdurrab, 2026)
Klebsiella sp and Shigella sp are rod-shaped gram-negative bacteria that are often found in the context of public health. Klebsiella sp is a pathogenic bacterium and can cause diarrhea, pneumonia infections, urinary tract infections, wound infections, meningitis to bacteremia. while Shigella sp is a pathogenic bacteria that causes dysentery diarrhea characterized by acute diarrhea containing blood and mucus, accompanied by abdominal pain and tenesmus, which is spread through contaminated food and drinks. Prevention of diarrheal diseases and respiratory tract infections caused by bacteria can be prevented by using antibiotics, but excessive use of antibiotics can lead to side effects. So natural treatment is used, namely papaya flowers because papaya flowers contain saponins, tannins and flavanoid compounds. The purpose of this study was to determine the antibacterial inhibition of papaya flower extract at a concentration of 35%, 50%, 65% against Klebsiella sp and Shigella sp. This study is an experimental research using a quantitative descriptive test method. The sample of this study is papaya flower extract on the growth of Klebsiella sp and Shigella sp. bacteria. The test method used is sub-diffusion. The results showed that the concentration of 65% was the most effective concentration to inhibit the growth of Klebsiella sp and Shigella sp bacteria with a yield of 27.6 mm which was in the medium category. Papaya flower extract has antibacterial compounds (flavonoids, tannins and saponins) that are able to inhibit the growth of Klebsiella sp and Shigella sp bacteria.